Study of the molecular structure, electronic structure, spectroscopic analysis and thermodynamic properties of dibenzofuran using first principles - Uprety, Roshika; Ghimire, Rabin; Gharti Magar, Pima; Rokka, Dilip; Khadka, Ishwor Bahadur; Neupane, Rajendra; Rai, Krishna Bahadur (Journal of Nepal Physical Society, 2024)
This study examines the different properties of dibenzofuran using density functional theory (DFT) B3LYP/6-311G(d, p) basis set. In dibenzofuran molecules, seven steps are required to establish an optimized energy setup. The HOMO-LUMO energy gap is found to be 5.028 eV. The value of global reactivity parameters i.e. chemical potential (μ), electronegativity (χ), global hardness (η), global softness (ζ) and electrophilicity (ω) are found to be - 3.751 eV, 3.751 eV, 2.514 eV, 0.398 (eV)-1 and 2.798 eV respectively. The observed energy gap in the DOS spectrum for the dibenzofuran is 4.992 eV which is almost equal to the HOMO-LUMO energy gap. Mulliken charges with the C3 and C7 atoms are observed with the highest positive charges along with some positive charges on all the hydrogens atoms while oxygen O21 shows the highest negative charge together with some negative charges on C1, C2, C4, C5, C6, C8, C9, C10, C11 and C12 atoms. The MEP and ESP showed that there is negative potential localized around the benzene ring and oxygen atom showing nucleophilic region. In contrast, the positive potential is localized around the hydrogen atom showing an electrophilic region. Electron density shows the uniform charge distribution. The observed peak values for the C-C vibrations are at 1471 cm-1 and 1484 cm-1, C-H vibration are at 3191 cm-1, and C-O vibration is at 1215 cm-1. Thermodynamic parameters like heat capacity at constant volume and constant pressure, internal energy, enthalpy and entropy increase with the rise in temperature i.e. from 10 K to 500 K and Gibbs free energy decreases with the same increase in temperature.